Media Framing of Online Reporting: Budget Efficiency of the National Library of the Republic of Indonesia - Nofalita, Nofalita; Aulia Rissa N (Jurnal Multidisiplin Sahombu, 2025)
The budget efficiency policy is outlined in Presidential Instruction No. 1 of 2025 has generated diverse public reactions, including from the literacy and cultural sectors. The mass media play a crucial role in shaping public perceptions of this policy through the way news is constructed and presented. This study aims to analyze how Indonesian online media frames the issue of budget efficiency affecting the National Library of the Republic of Indonesia (Perpusnas RI). A qualitative approach was employed using the framing analysis model of Pan and Kosicki, which includes four dimensions: syntactic, script, thematic, and rhetorical structures. Three national online media outlets—Kompas.com, Liputan6.com, and Tempo.co—were selected as research objects to represent variations in media ideology and reporting style in Indonesia. The results reveal significant differences in framing among the three media. These differences in framing indicate that media coverage not only conveys information but also constructs social reality and public opinion in line with each outlet's editorial ideology. This study underscores the importance of media literacy, enabling the public to interpret news critically and avoid being confined to a single perspective.